Production of enriched protein extracts from cultivated Ulva sp. (Chlorophyta, Ulvales) by high-pressure homogenization - Déniel Luque, Anna; Pliego-Cortés, Hugo; Burlot, Anne-Sophie; Terme, Nolwenn; Furic, Marie; Bourgougnon, Nathalie (Frontiers in Marine Science, 2025)
The human food sector plays a crucial role in supporting population growth and ensuring human well-being. In the context of global food security, environmental challenges, and the diversification of protein sources, research into new innovative and sustainable protein sources is essential. In Europe, alternative protein sources such as cultivated seaweed are a promising solution, with potential health benefits and increased sustainability. This study investigated the use of high-pressure homogenization (HPH) to obtain protein-enriched fractions from dried biomass of cultivated Ulva sp. The biochemical composition, physical-chemistry (FTIR and granulometric analysis) and the biological activities of the supernatant and residue fractions were evaluated after HPH treatment at pressures of 0, 600, 800, and 1000 bars. Results showed that, depending on their nature, pressure significantly influenced the biochemical composition and separation of compounds into the residue and supernatant, and underlined the potential of HPH to enhance protein recovery from Ulva sp. HPH facilitated separation of ulvan polysaccharides, known for their anti-nutritional effects, and from the protein fraction with high recovery yields of 60.0% protein in the residue. The highest protein content was found in residues at 1000 bars (8.93%) compared to in the crude extract (4.1%). Amino acid analysis revealed that essential amino acids accounted for 42% of total amino acids in the Ulva sp. fraction, with high levels of valine, leucine and methionine. The ulvan fraction (concentration of rhamnose, uronic acids and sulphate groups) was preferentially extracted at 1000 bars, where the supernatants contained 28.6 ± 4.5% of uronic acids, 23.2 ± 4.9% of sulfate groups, and 3.72 ± 0.31% of rhamnose (p< 0.05).These results provide clear evidence that HPH is effective in disrupting the cell wall and facilitating the release of compounds of interest. These results also suggest that the HPH process could position cultivated Ulva sp. as an important potential source of food protein.